Evaluation of the α2-adrenergic Agonist Mafedine Effects on White Outbred Mouse Behaviour Following Acute Administration - N. S. Kurmazov; S. A. Chervonetskiy; V. A. Prikhodko; Yu. I. Sysoev; S. V. Okovityi (Разработка и регистрация лекарственных средств)
Introduction. α2-adrenergic agonists are not only used as antihypertensive and sedative agents, but are also of interest as potential medications for the treatment of neurological disorders. Previous research has shown a compound from this class, 6-oxo-1-phenyl-2-(phenylamino)-1,6-dihydropyrimidine-4-ol (mafedine), to exert strong neuroprotection under experimental conditions. Despite its long record of development, the effects of mafedine on animal behavioural characteristics remain unknown.Aim. This work was aimed at evaluating the effects of mafedine sodium at three doses (1, 10, or 50 mg/kg) on white outbred mouse behavior in three tests: Open Field, Elevated Plus Maze, and Light/Dark Box.Materials and methods. Experiments were carried out on 60 white outbred male mice weighing 20–22 g, randomized into 4 groups (n = 15): 1) control (0,9 % saline); 2) mafedine (1 mg/kg); 3) mafedine (10 mg/kg); 4) mafedine (50 mg/kg). All agents were administered via single intraperitoneal injections 20 min before testing. Animal behavior was assessed using the Open Field, Elevated Plus Maze, and Light/Dark Box tests following conventional protocols with group reassignment between tests and an inter-test time interval of at least 2 days. Statistical analysis was carried out using the Prism 8.0.2 software package.Results and discussion. At 1 or 10 mg/kg, mafedine did not affect animal behaviour in either of the tests. At 50 mg/kg, it produced an anxiolytic effect, as indicated by the decrease in the anxiety index values for the Elevated Plus Maze test as well as the increase in peeking out frequency in the Light/Dark Box test, compared to respective control values.Сonclusion. Mafedine sodium salt at doses between 1 and 50 mg/kg was shown to produce no adverse effect on mouse behaviour, indicating a good safety profile of the compound. The discovered anxiolytic effect of mafedine at the highest dose validates its further research not only as a neuroprotector, but also as an anti-anxiety agent.